Monomeric group 13 metal(I) amides: enforcing one-coordination through extreme ligand steric bulk - Dange, Deepak; Li, Jiaye; Schenk, Christian (Inorganic chemistry, 2012)
Reactions of the extremely bulky amido alkali metal complexes, [KL′(η6-toluene)], or in situ generated [LiL′] or [LiL″] {L′/ L″ = N(Ar*)(SiR3), where Ar* = C6H2{C(H)Ph2}2Me-2,6,4 and R = Me (L′) or Ph (L″)} with group 13 metal(I) halides have yielded a series of monomeric metal(I) amide complexes, [ML′] (M = Ga, In, or Tl) and [ML″] (M = Ga or Tl), all but one of which have been crystallographically characterized. The results of the crystallographic studies, in combination with computational analyses, reveal that the metal centers in these compounds are one coordinate and do not exhibit any significant intra- or intermolecular interactions, other than their N-M linkages. One of the complexes, [InL′], represents the first example of a one-coordinate indium(I) amide. Attempts to extend this study to the preparation of the analogous aluminum(I) amide, [AlL′], were not successful. Despite this, a range of novel and potentially synthetically useful aluminum(III) halide and hydride complexes were prepared en route to [AlL′], the majority of which were crystallographically characterized. These include the alkali metal aluminate complexes, [L′AlH2(μ-H)Li(OEt2)2(THF)] and [{L′Al(μ-H)3K}2], the neutral amido-aluminum hydride complex, [{L′AlH(μ-H)}2], and the aluminum halide complexes, [L′AlBr2(THF)] and [L′AlI2]. Reaction of the latter two systems with a variety of reducing agents led only to intractable product mixtures.
Gesehen am 11.07.2018